Dealing with Disasters : Analyzing Vanuatu’s Economy and Public Finances Through the Lens of Disaster Resilience - World Bank (Washington, DC, 2022)
This report provides a selected analysis of Vanuatu’s economy and public finances, emphasizing the lens of disaster resilience. It draws upon the analysis and tools from two core World Bank diagnostic products, the Country Economic Memorandum (CEM) and Public Expenditure Review (PER) while bringing the depth and breadth of the analysis to scale with country context and key constraints. In terms of the economic analysis, the report first examines the country’s recent economic performance, followed by an analysis of the agriculture sector, labor mobility, and the tourism sector. In terms of public expenditure analysis, the report first discusses overall fiscal trends and prospects, after which the overarching Public Financial Management (PFM) framework is analyzed. The report concludes with an analysis of public spending in the education and health sectors.